Changes in selected locomotor skills of young runners after one athletic season: Influence of sex and age. Issue 5 (October 2021) - Rodriguez-Negro, Josune; Llodio, Iñaki; Castillo, Daniel; Romaratezabala, Estibaliz; Yanci, Javier
The aim of the present research was to describe the changes in the locomotor competence [i.e. sprint, change of direction ability (CODA) and jump capacity] of young runners from an athletic training school after one season, according to runners' sex and age. Two hundred and forty-one young runners from an athletic training school were divided by sex (boys, n = 107, and girls, n = 134) and age [under 8 years old (U8, n = 70), under 10 years old (U10, n = 68), under 12 years old (U12, n = 45), under 14 years old (U14, n = 39) and under 16 years old (U16, n = 19)]. At the start of the training season (PRE) and at the end of the season (POST), the runners performed different tests in order to assess their locomotor competence. The results showed that boys and girls improved their performance during the season in the 5 m sprint ( p  = 0.000, ES = -0.58 to -0.74) and horizontal countermovement jump (HCMJ) ( p  = 0.000, ES = 0.51 to 1.02), and decreased it in the 15 m sprint test ( p  = 0.011 or p  = 0.006, ES = 0.27 to 0.31), and only girls improved in change of direction ability (CODA) ( p  = 0.000, ES = -0.22 to -0.27). In addition, with respect to age categories, all groups improved their performance in the HCMJ ( p  = 0.000 - 0.005, ES > 0.40) and the 5 m sprint tests ( p  = 0.000 - 0.002, ES = -0.68 to -1.24). Although in the 505 test no group improved its result ( p  = 0.184 - 0.314, ES = -0.25 to 0.01), the U8 and U10 groups improved in the modified agility test (MAT) ( p  = 0.000 or p  = 0.003, ES = -0.38 to -0.41). In conclusion, there are differences in the changes in the locomotor competence according to runners' sex and age, so perhaps age- and sex-dependent specialization in training is necessary.